Immunomodulatory and growth-promoting effects of Rauwolfia serpentina root powder in broiler chicks challenged with Salmonella Gallinarum - Zhang, Yingyu; Rehman, Hiba; Khattak, Farina; Tariq, Maryam; Khan, Bushra Nisar; Chaman, Sadia; Riaz, Ayaesha; Ovais Omer, Muhammad; Ali, Aqib; un Nisa, Qamar; Muddassir Ali, Muhammad; Saleem, Gulbeena (Frontiers in Veterinary Science, 2025)
BackgroundAmid growing concern about antimicrobial resistance due to the irrational use of antibiotics in treating common poultry diseases, particularly Salmonella which is a foodborne pathogen in humans. This study investigates the effects of ethnoveterinary supplementation of Rauwolfia serpentina (L. Benth. ex Kurz) powder (RSP) on three key immune-related genes; Suppressor of cytokine signaling 3 (SOCS3), the quiescence-related gene P20K (P20K), and the major histocompatibility complex Class IIβ (MHC class IIβ), gut morphology and growth performance of broiler chicks infected with Salmonella Gallinarum.MethodsTwo hundred and forty day-old Hubbard classic chickens were randomly assigned to four groups: non-challenged control (NC), and Salmonella Gallinarum challenge group (SGC), and two treatment groups fed a basic diet supplemented with 1.5% Rauwolfia serpentina powder (RSP) with SGC (RSP-1) and 3% RSP with SGC (RSP-2), respectively, from day 3 till 28 days of age. Each treatment was replicated 4 times with 15 bird/replicate pen. On day 7, all the birds in the RSP-1, RSP-2 and SGC groups received 1 ml of BHI broth containing 2 × 108 CFU of Salmonella Gallinarum via oral gavage. While control birds received an equivalent volume of sterile BHI broth. Gene expression analysis was conducted using real-time PCR to measure the expression of key immune-related genes: SOCS3, P20K, and MHC Class IIβ in spleen, liver, and caeca. Additionally, histopathological assessments of gut and growth performance parameters including feed intake, body weight gain, and feed conversion ratio (FCR) were monitored throughout the experimental period.ResultThe gene expression analysis at 3 and 21 days post-challenge revealed that SGC birds had significantly higher SOCS3, P20K, and lower MHC class IIβ expression (p < 0.001) in the caecum, liver, and spleen of broiler chickens. In contrast, the RSP-1 and RSP-2 groups showed significantly lower SOCS3 and P20K expression (p < 0.001), alongside improved gut morphology, weight gain, and FCR compared to the SGC group, with these benefits increasing over time.ConclusionIn conclusion, these findings suggest that Rauwolfia serpentina supplementation modulates key immune-related gene expression (SOCS3, P20K, and MHC class IIβ), enhances intestinal health, and improves growth performance in broilers challenged with Salmonella Gallinarum.